The theory of externalities, public goods, and club goods - Cornes, Richard; Sandler, Todd (Cambridge Univ. Pr., 1986)
This book presents a theoretical treatment of externalities (i.e., uncompensated interdependencies), public goods, and club goods. Aimed at advanced undergraduate and graduate students making their first serious foray into this branch of economics, the book will also interest professional economists wanting to discover what their colleagues in public economics have been working on in recent years. As such, it attempts to tie together the most recent contributions in public economics, available in many diverse sources. The book will be suitable for courses concerned with public expenditure analysis, where no other single source for this material is currently available. Applications, theory, and policy aspects of public expenditure analysis are presented. Useful new graphical tools are also included. Among the topics included are: Nash equilibria, Lindahl equilibria, club theory, preference-revelation mechanisms, Coase theorem, externalities, and game theory.
Keywords: Bienes públicos; Biens collectifs; Welvaartstheorie; Économies externes; Externalities (Economics); Public goods; Theorie; Öffentliches Gut; Externer Effekt; Wirtschaftstheorie; Ökonomische Theorie des Clubs; Einführung